Exploring the Outcomes of Portal Vein Thrombosis in the Clinical Setting of Cirrhosis, Malignancy, and Intra-abdominal Infections with and without Anticoagulation: A Retrospective 5-Year Study - Sule, Ashish Anil; Joseph, Joanne B.; Chew, Samuel C. J.; George, Julie; Chin, Tay Jam (International Journal of Angiology, 2018)
The aim of this study was to understand the differences in clinical outcomes in portal vein thrombosis (PVT) patients with cirrhosis, malignancy, and abdominal infections, with or without anticoagulation. This study was approved by ethics committee. Data were collected from 2011 to 2016. Patients were classified into three groups: PVT with cirrhosis, malignancy, and infections. Primary outcomes measures collected were clot resolution, bleeding, recurrence, and death. Frequency, means, and percentages were calculated. In total, 30 patients were analyzed in this study. Mean age was 60.8 years (range of 30–91 years). There were 19 (63.3%) males and 11 (36.7%) females with ethnicity: 21 (70.0%) Chinese, 2 (6.7%) Malay, 2 (6.7%) Indian, and 5 (16.7%) other race. Fifteen patients received anticoagulation and 15 did not receive anticoagulation. Of the 15 patients who received anticoagulation, there was complete resolution of thrombus in 5 (33.3%), partial resolution in 1 (6.7%), and no resolution in 9 (60.0%). Of these 15 patients, there was bleeding in 3 (20.0%), there was no recurrence in 9 (60.0%), and 3 (20.0%) died during the period of follow-up. Of the 15 patients who did not receive anticoagulation, there was complete resolution of thrombus in 2 (13.3%), partial resolution in 0 (0.0%), and no resolution in 13 (86.7%). Of these 15 patients, there was bleeding in 0 (0%), there was recurrence in 2 (13.3%), and 6 (40.0%) died during the period of follow-up. Anticoagulation is effective in PVT. It reduces mortality with lower rate of recurrence. However, it is associated with increased risk of bleeding.
Keywords: thrombophilia; portal vein thrombosis; anticoagulation; low molecular weight heparin